Analysis of Tumor Buds & Worst Pattern of Invasion as Emerging Factor in Determining Lymph Node Metastasis in Oral Squamous Cell Carcinoma - Goswami, Parth Rajendragiri; Goswami, Alpeshpuri P (Annals of Pathology and Laboratory Medicine, 2020)
Introduction Lymph node metastasis is associated with poor prognosis in oral squamous cell carcinoma. So, it’s important to identify most influencing histological parameter in association with lymph node metastasis. Aim Of Study: The aim of this study is to analyze various histological parameter including tumor buds and worst pattern of invasion to check its association with lymph node metastasis positive cases. Materials & Methods The study done on 100 oral squamous cell carcinoma patients. The various histopathological parameters like Nuclear Pleomorphism, Number of mitosis, Lymphoplasmacytic inflammation along with tumor buds and WPOI analyzed to check association with node metastasis. The data was tabulated and Fischer’s exact & chi square test applied to calculate p value. Result Invasive tumor buds more than 5 and worst pattern of invasion (WPOI) were strongly associated with positive lymph node metastasis cases. The p value for both has been lowest among all other parameter. Conclusion The tumor buds and Pattern of invasion are most important emerging influencing factor having strong association with nodal metastasis and thus high risk patient can be identified in biopsy specimen.